The territorial peculiarities of road traffic injury in Ukraine - Корнус, А.; Корнус, О. (Київський національний університет імені Тараса Шевченка, 2016)
The analysis of the number of road traffic accidents, injuries and deaths in road crashes was conducted at the regional level. This made it possible to draw conclusions about specific features of spatial distribution of these indicators and the non-accidental nature of their implications for different regions of Ukraine. Based on the methods of spatial statistics and we have demonstrated the existence of spatial patterns in the distribution of risks and consequences of accidents in different regions. Statistical analysis allowed us to identify different types of regions, related to certain categories of risks, injuries and deaths from road accidents. By the analysis of these parameters we were calculated the comprehensive index of road safety for all regions of Ukraine. This allows you to evaluate the complex influence of consequences of accidents on the overall security level of the population of certain regions or groups of regions. The safest roads were in city of Kyiv, Transcarpathian region and city of Sevastopol’, as well as in Ivano-Frankivs’k and Kharkiv regions. The worst state of roads and streets in terms of road accidents and their consequences was in Volyn’, Vinnytsia, Chernihiv, Khmelnytsky and especially in Kherson region. Most of the road crashes were due to driver factors. The percentage of accidents with victims occurred due to fault of drivers in 2013 was ranged from 57.28% in Kyiv to 91.19% in Kharkiv region. The main causes are speeding, unsuccessful maneuvering, unsafe lane changes, violation of rules on intersection or marked crosswalk, driving a vehicle while intoxication through drink or drugs. As a result of these violations in Ukraine committed about 55% of accidents. Due to fault of pedestrians is done much less road accidents than because of due to drivers. The proportion of accidents that have occurred due to pedestrians varies from 6.49% in Transcarpathian region to 20.86% in Mykolaiv region. The main causes of accidents of this type in 2013 are hit by car outside pedestrian crossing (2183 accidents and 449 deaths) and an unexpected appear of pedestrians on the roadway (1495 accidents and 409 fatalities). The results of the study can be used to improve national and regional road and transport safety, and to develop strategies and actions to reduce the risks and consequences of accidents in some regions. It should be more detail to establish the reasons behind the emergence of these factors at the local, regional and national levels and, taking those reasons into account, to develop a set of targeted measures to reduce accidents on the roads and reduce the severity of their consequences.

У статті виконано аналіз кількості дорожньо-транспортних пригод, а також рівня травматизму і смертності у них на рівні регіонів України. На основі методів просторової статистики показано існування географічних особливостей у розподілі частоти і наслідків дорожньо-транспортних пригод у різних регіонах. Розрахований у роботі індекс дорожньої безпеки дозволив розподілити регіони за рівнем травматизму і смертності унаслідок дорожньо-транспортних пригод. На основі аналізу цих показників зроблено комплексну оцінку рівня дорожньої безпеки для регіонів України. Результати проведених досліджень можуть бути використані для вдосконалення регіональних програм організації дорожнього руху і підвищення рівня транспортної безпеки, а також для розробки стратегій і дій, спрямованих на зниження ризиків і наслідків дорожньо-транспортних пригод у деяких регіонах.
Територіальні особливості дорожньо-транспортного травматизму в Україні
Avramenko V.V., Syutkin S.I. Osoblyvosti dorozhn’o-transportnykh pryhod na avtoshlyakhakh Ukrayiny zalezhno vid rivnya sotsial’no-ekonomichnoho rozvytku rehioniv ta yikh turystychnoyi spryamovanosti [Peculiarities of the accidents on the roads Ukraine depending on the socio-economic development of regions and their tourism focus] // Naukovi zapysky SumDPU imeni A. S. Makarenka. Heohrafichni nauky. – 2015. – Issue 6. – рр. 158-169. [in Ukrainian] Lyebyedyeva T.L. Problemni pytannya bezpeky dorozhn’oho rukhu v Ukrayini (povidomlennya 1) [Problems of road safety in Ukraine (1stannouncement)] // Journal of Education, Health and Sport. – 2015. – Vol. 5(6). – рр. 472-481. [in Ukrainian] Myronenko S.V., Myronenko K.S. Analyz vlyyanyya urovnya avaryynosty v Ukrayne na obshchuyu tendentsyyu dorozhno-transportnoy sytuatsyy [Analysis of the impact of the accident rate in Ukraine, the general trend of road traffic situation] // Informatsiyni tekhnolohiyi v osviti, nautsi ta vyrobnytstvi. – 2013. – Issue 3(4). – рр. 59-65. [in Russian] Polishchuk H. Heohrafiya ta dynamika DTP, skoyenykh z vyny ditey u 2014 rotsi [Geography and dynamics of the road accidents, committed due to of children in 2014]. Available at: http://infolight.org.ua/content/geografiya-ta-dynamika-dtp-skoyenyh-z-vyny-ditey-u-2014-roci [in Ukrainian] Statystyka avariynosti v Ukrayini [Statistics of accidents in Ukraine]. Available at: http://www.sai.gov.ua/ua/ua/static/21.htm [in Ukrainian] Statystyka DTP u 2014 rotsi: de ta chomu? [Accident statistics in 2014: where and why?] Available at: http://infolight.org.ua/content/statystyka-dtp-u-2014-roci-de-ta-chomu [in Ukrainian] Statystychnyy shchorichnyk Ukrayiny za 2014 rik [Statistical yearbook of Ukraine for the year 2014]. – K., 2015. [in Ukrainian] Shyshchuk V., Kornus A., Kornus O., Dominas V. Dorozhniy travmatyzm ta rehional’na systema travmatolohichnoyi dopomohy: medychnyy ta terytorial’nyy aspekty (na prykladi Sums’koyi oblasti) [Road traffic injuries and regional system of trauma care: medical and territorial aspects (case study of Sumy region)] // Journal of Education, Health and Sport. – 2016. – Vol. 6 (9). – рр. 460-470. [in Ukrainian] Shchorichna dopovid’ pro stan zdorov’ya naselennya, sanitarno-epidemiolohichnu sytuatsiyu ta rezul’taty diyal’nosti systemy okhorony zdorov’ya Ukrayiny. 2014 rik / Za red. O. Kvitashvili [Annual report on the state of health, sanitary and epidemiological situation and the results of the health system activity in Ukraine for the year 2014 / Ed. by O. Kvitashvili]. – K., 2015. [in Ukrainian] Global status report on road safety 2015 / World Health Organization. [Available at:: http://apps.who.int/iris/bitstream/10665/189242/1/9789241565066_eng.pdf [in English] Murray C. at al. Alternative Projections of Mortality and Disability by Cause 1990-2020: Global Burden of Disease Study // The Lancet. – №349. – Р. 498-1504 [in English] Road safety in Ukraine (2012) / UNECE. Available at: https://www.unece.org/fileadmin/DAM/trans/roadsafe/unda/Sweden_Ukraine.pdf [in English]
Keywords: дорожньо-транспортні пригоди; травматизм; смертність; індекс дорожньої безпеки; територіальна структура; Україна; road traffic accident; injury; mortality; road safety index; territorial structure; Ukraine